Adapting the local response for malaria elimination through evaluation of the 1-3-7 system performance in the China–Myanmar border region. (December 2017) - Wang, Duoquan; Cotter, Chris; Sun, Xiaodong; Bennett, Adam; Gosling, Roly; Xiao, Ning
Abstract Background Assessing the essential components of '1-3-7' strategy along the China–Myanmar border is critical to identify gaps and challenges to support evidence-based decision making. Methods A mixed-method retrospective study including quantitative and qualitative analysis of the 1-3-7 system components was conducted. Sampled counties were chosen based on malaria incidence from 1 January 2012 to 31 December 2014. Results All 260 confirmed malaria cases from sampled counties were reported within 1 day and had completed case investigations. 70.0% of all Reactive Case Detection (RACD) events were conducted and 90.1% of those were within 7 days. Only ten additional individuals were found malaria positive out of 3662 individuals tested (0.3%) by rapid diagnostic test during RACD events. Conclusions Key gaps were identified in case investigation and RACD activities in Yunnan Province border counties. This evidence supports improving the RACD (or "7") response strategy in this setting. Given the challenges in this border region, it will be critical to adapt the RACD response to promote the malaria elimination along the China border.